2013
DOI: 10.1038/nature12188
|View full text |Cite
|
Sign up to set email alerts
|

Mitonuclear protein imbalance as a conserved longevity mechanism

Abstract: Longevity is regulated by a network of intimately linked metabolic systems. We used a combination of mouse population genetics and RNAi in C. elegans to identify mitochondrial ribosomal protein S5 (Mrps5) and other mitochondrial ribosomal proteins (MRPs) as metabolic and longevity regulators. MRP knockdown triggers mitonuclear protein imbalance, reducing mitochondrial respiration and activating the mitochondrial unfolded protein response (UPRmt). Specific antibiotics targeting mitochondrial translation and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
1,072
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 908 publications
(1,179 citation statements)
references
References 47 publications
59
1,072
10
2
Order By: Relevance
“…Interestingly, these interventions were then found to trigger the mitochondrial unfolded protein response (UPR mit ) that contributes to the observed lifespan extension (Durieux, Wolff, & Dillin, 2011). Similar observations were also described in mice (Houtkooper et al, 2013; Jovaisaite, Mouchiroud, & Auwerx, 2014). …”
Section: Resultssupporting
confidence: 85%
“…Interestingly, these interventions were then found to trigger the mitochondrial unfolded protein response (UPR mit ) that contributes to the observed lifespan extension (Durieux, Wolff, & Dillin, 2011). Similar observations were also described in mice (Houtkooper et al, 2013; Jovaisaite, Mouchiroud, & Auwerx, 2014). …”
Section: Resultssupporting
confidence: 85%
“…Doxycycline was obtained from Sigma-Aldrich and dissolved in water 23 . For experiments, a final concentration of 15 μg/mL was used.…”
Section: Methodsmentioning
confidence: 99%
“…Given the tight link between the UPR mt and AD observed above, we investigated the effects of two established strategies to induce the UPR mt in C. elegans ; genetically, by silencing the expression of the mitochondrial ribosomal protein mrps-5 23 , and pharmacologically, by using the mitochondrial translation inhibitor doxycycline (dox) 23,24 . Both interventions, which favor worm health and lifespan 23 , markedly induced transcripts of UPR mt , mitophagy and respiration genes in GMC101 (Fig.…”
Section: Reducing Mitochondrial Translation Lowers Aβ Proteotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, using the CNV approach, we found that the majority of complex I members do not change significantly relative to the rest of mitochondrial proteins (Fig 3D, right panels, and Dataset EV6). We instead revealed two members of the complex I (the nuclear‐encoded NDUF‐2.2 and the mitochondrial‐encoded ND5) that showed extreme and opposite CNV values, suggesting loss of stoichiometry due to mitonuclear imbalance (Fig 3E; Houtkooper et al , 2013). Similarly, the abundance of mitochondrial ribosome components was suggested to be decreasing with age.…”
Section: Resultsmentioning
confidence: 84%